The complete mitochondrial genome of Achatinella mustelina (Gastropoda: Pulmonata: Stylommatophora). Issue 1 (1st January 2016) - Price, Melissa R.; Forsman, Zac H.; Knapp, Ingrid; Hadfield, Michael G.; Toonen, Robert J.
Abstract: In this study, we report the complete mitochondrial genome sequence of Achatinella mustelina, an endangered Hawaiian tree snail. The mitogenome is 16 323 bp in length and has a base composition of A (34.7%), T (42.6%), C (12.7%) and G (10.0%). Similar to other Pulmonates, it contains 13 protein-coding genes, 2 rRNA genes and 22 tRNA genes. To our knowledge, this is the first mitochondrial genome sequenced within the Achatinelloidea superfamily, which contains a high number of endangered species. As such, this mitogenome will be useful in conservation genetics studies.